THE EXISTENCE OF CONSTITUTIONAL COURT DECISIONS IN THE HIERARCHIES OF LEGISLATION IN INDONESIA - Geofani Milthree Saragih (NOMOI Law Review, 2023)
The Constitutional Court is one of the state institutions in Indonesia that exists within the jurisdiction of the judiciary. The main background for the birth of the Constitutional Court in Indonesia is the result of a change from an authoritarian government system to a democratic one. The existence of the Constitutional Court is expected to provide significant restrictions on the formation of laws in Indonesia which are considered to be tools that are misused by certain oligarchs in fulfilling the interests of their groups. As was the conclusion of Mahfud MD's dissertation which said that basically politics determines law. The discussion in this chapter will examine the existence of the Constitutional Court's decision in terms of reviewing laws against the 1945 Constitution in the hierarchy of laws and regulations in Indonesia. Broadly speaking, the discussion will be divided into three sub-chapters, first , regarding the background of the birth of the Constitutional Court in Indonesia and the powers it has, second , the hierarchy of laws and regulations in Indonesia, third , the existence of the Constitutional Court's decision in reviewing laws against laws Basic 1945 in the hierarchy of laws and regulations in Indonesia. The main conclusion from the discussion of this sub-chapter is to emphasize that basically the decision of the Constitutional Court greatly influences the existence of a law that is being enacted, because the Constitutional Court can negate a law that is considered contrary to the 1945 Constitution. This fact can affect other legal products contained in the hierarchy of laws and regulations in Indonesia, especially those under the law and which have the same status as the law, namely government regulations in lieu of laws.